The Role of Actors in The Desa Siaga Program in Watupute Village, Mowewe Subdistrict, East Kolaka - Murni Ratna Sari Alauddin ,; Suryo Ediyono ,; Asep Irwanto, (International Journal Of Health Science, 2023)
This research aims to analyze the role of each actor involved in realizing health services so as to be able to find out each actor's perspective regarding health services through the Desa Siaga in Watupute Village. Apart from that, it is necessary to determine the actions of each actor in order to improve the health service system in Watupute Village. This research method is descriptive-qualitative by determining the research sample using purposive sampling, data collection through observation, document study, interviews with several actors involved in this program, and data analysis using the Miles and Huberman model. The results of this research were able to identify the actors involved in health services in Watupute Village, namely, the Health Departement of East Kolaka, Desa Siaga cadres, Watupute village government, and the Watupute village community. Each actor has a role in developing health services through Desa Siaga. However, there are still actors who cannot carry out their roles, so achievements in program implementation are not optimal. In determining actions, the Health Office of East Kolaka has determined regulations that must be obeyed in implementing the Desa Siaga, the Watupute Village Government has provided a budget that comes from village funds, the Desa Siaga cadres have carried out their duties in implementing the Desa Siaga, and the community has participated in the success of the village program. Standby. Based on the results of this research, the researcher suggests equalizing perceptions between actors so that there is a understanding and health services in Watupute village can run effectively.